The optimal number of examined lymph nodes for accurate nodal staging and favorable prognosis of oral tongue squamous cell carcinoma. (May 2023) - Zhuge, Lingdun; Cai, Huizhu; Huang, Zehao; Wang, Shixu; Li, Zhengjiang
Highlights: Firstly reported optimal number of examined lymph nodes in oral tongue squamous cell carcinoma. Use the correlation of each examined lymph node count with nodal migration and OS to identify optimal cut point. Based on a large number of population and verified in two data sets. Abstract: Objective: The study aimed to determine the optimal count of examined lymph nodes (ELN) for accurate assessment of lymph node status and favorable long-term survival in patients with oral tongue squamous cell carcinoma (OTSCC) who received radical resection. Methods: Patients with OTSCC who received radical resection between 2004 and 2015 were enrolled from the Surveillance, Epidemiology, and End Results database (SEER) and were randomly divided into two cohorts. The association of ELN count with nodal migration and overall survival (OS) was analyzed using a multivariate regression model with the adjustment of relevant factors. Locally weighted scatterplot smoothing (LOWESS) and 'strucchange' package were adopted to identify the optimal cut points using R. Results: A total of 2077 patients were included in this study. The optimal cut points of ELN count for accurate nodal staging and favorable OS were 19 and 15, respectively. The probability of detecting positive lymph nodes (PLN) significantly increased in patients with ELN count ≥ 19 in comparison to those with ELN count < 19 (training set, P < 0.001; validation set, P = 0.012). A better postoperative prognosis was observed in patients with ELN count ≥ 15 than those with fewer ELN (training set, P = 0.001, OR: 0.765; validation set, P = 0.016, OR: 0.678). Conclusion: The optimal cut point of ELN count to ensure the accuracy of nodal staging and to achieve a favorable postoperative prognosis were 19 and 15, respectively. The ELN count beyond the cutoff values might improve the accuracy of cancer staging and OS.